Analysis of Internal Control of Bad Receivables - Safrizal, Safrizal; Sumiyati, Sumiyati (Talent: Journal of Economics and Business, 2024)
The purpose of this research is to find out whether the internal control of bad debts at the company PT. X is running well. Because basically selling on credit also carries the risk of uncollectible portions of the receivables or even all of the receivables. Companies often face challenges in recovering debts from customers, especially in cases of credit sales, which gives rise to the phenomenon of bad debts. This phenomenon results in significant financial risk, with the possibility of partial or even complete loss of receivables. In this research, the analytical approach used is a qualitative descriptive method, which utilizes primary data obtained through interviews with PT management. X. This study provides a deep picture of how the company responds to and handles the risk of uncollectible receivables and how effective the company's internal control is in preventing and reducing this problem. The results of this research indicate that although the implementation of internal control at PT. X goes well but there is a failure in recovering some receivables, which results in uncollectible receivables. This situation is caused by various factors such as company policy, poor internal control, weak credit evaluation and other things. These findings highlight the importance of improving strategy and internal control in receivables management, to avoid the accumulation of bad debts and their negative impact on the company's financial position